PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIB SDN 136 PEKANBARU - Dia Istiqamah; Zariul Antosa; Lazim N Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this study is the low learning achievement of social science of grade IIIB SDN 136 Pekanbaru. This can be seen from the average daily test of 59.03 out of 31 students. While the minimum completeness criteria (KKM) that has been determined primary school that is 75. This study aims to improve student learning outcomes IPS of grade IIIB SDN 136 Pekanbaru with the application of Quantum Teaching model. This type of research is Classroom Action Research (CAR). This research was conducted at SDN 136 Pekanbaru with sample of student of grade IIIB student which amounted to 31 students. Based on the research result, it is found that teacher activity in every learning has increased, that is in cycle I 80% and in cycle II also increase with teacher activity average become 85%. Student activity also increase in each learning, this can be proved by the average of student activity in cycle I 61,36% and in cycle II rose to 70,45%. Based on the scores of student learning outcomes in a classical there is an increase in the number of students who reach the minimum completeness criteria (KKM) that is on the first cycle of the percentage of 74.19% while in the second cycle of completion classical students 93.54%. Application of Quantum Teaching model can improve student learning result of grade IIIB SDN 136 Pekanbaru this matter can be seen from average score base is 59,03 in cycle I increase become 73,06 with 23,76% increase then cycle II increase to 89, 19 with an increase of 51.09%.Keywords: Quantum Teaching, Social Studies Learning